The GzMYB-7D1 gene of Guizimai No.1 wheat is essential for seed anthocyanins accumulation and yield regulation - Luo, Jie (Plant science : an international journal of experimental plant biology, 2022)
Copyright © 2022 Elsevier B.V. All rights reserved.